Experiencing Historical Fiction Graphic Novels to Teach Social Studies - Barbara J. McClanahan (Study and Scrutiny, 2022)
A small study was conducted to determine how preservice teachers in a social studies methods class responded to reading an historical fiction graphic novel in an in-class literature circle followed by an authentication project. Role/task sheets, reading journals, and one-on-one interviews provided data. Analysis showed that all participants were successful at some level in navigating the unique aspects of the graphic novel and all felt the graphic novel experience could be successfully translated to their classrooms. Results also suggested that participants with prior experience with graphic novels appeared to have a more positive experience with the project.